Students’ Acceptance On Educational Video Sharing Sit: A Proposed Research Model - Md Ali, Sazanah; Mohamad Ali, Ahmad Zamzuri (2016)

(untitled)
Video sharing site is becoming increasingly popular and is used as a platform for video-based learning and teaching. In line with the development of new media technologies nowadays, learning through video sharing sites has become a choice of preference amongst students to get access to learning materials in the form of videos such as screencast tutorials, video presentations, recordings of learning video, animations and so forth. However, the existence of video sharing sites that have a social media characteristic in them is negatively affecting the students' learning performance. Thus, a provision of video sharing site with a more formal educational characteristic should be established in order to facilitate a safer learning environment. This study was conducted to analyse the acceptance of students towards educational video sharing sites. By using Technology Acceptance Model (TAM) as the basic model for this study, the original attributes in TAM model such as perceived usefulness and perceived ease of use were put to the test in order to determine their effects on attitudes and intentions of the students to use educational video sharing sites. In addition to that, TAM model was also expanded by adding other factors such as psychological factors (enjoyment and motivation), social factors (social influence and subjective norm), technological factors (system performance and system accessibility) and organisational factors (facilitating condition and technical support). This conceptual paper was prepared to tested on how they affect students' acceptance towards educational video sharing site